MicroRNA-5112 Targets IKKγ to Dampen the Inflammatory Response and Improve Clinical Symptoms in Both Bacterial Infection and DSS-Induced Colitis - Kang, Xilong; Jiao, Yang; Zhou, Yingying; Meng, Chuang; Zhou, Xiaohui; Song, Li; Jiao, Xinan; Pan, Zhiming (Frontiers in Immunology, 2022)
Inflammation is a double-edged sword that can be induced by various PAMPs, resulting in the control of infection by invading pathogens or injuries. The inflammatory response requires strict and precise controll and regulation. MicroRNAs (miRNAs) are small non-coding RNA molecules that regulate gene expression via translational inhibition or mRNA degradation. However, the role of miRNAs in inflammation induced by flagellin (ligand of TLR5) has yet to be fully determined. In this study, we identified differentially expressed miRNAs in murine bone marrow-derived dendritic cells (BMDCs) between flagellin treatment and medium alone using miRNA microarray. We found that flagellin stimulation downregulated miR-5112 expression in BMDCs and spleen DCs in vitro and in vivo. The overexpression of miR-5112 decreased inflammatory cytokine production, accompanied by a reduction of IKKγ in flagellin-stimulated BMDCs. We demonstrated that miR-5112 could directly target IKKγ to inhibit inflammatory cytokine production. Furthermore, miR-5112 inhibited the inflammatory response induced by flagellin or Salmonella infection in vivo. Interestingly, miR-5112 could also dampen the inflammatory response and alleviate dextran sulfate sodium (DSS)-induced colitis in C57BL/6 mice. These results suggest that miR-5112 could be a novel therapeutic target for both bacterial infection and DSS-induced colitis model.